Performance of computer-assisted technology for manufacturing removable complete dentures and bars used in implant supported overdentures: systematics reviews - Chappuis Chocano, Ana Paula (2022)
The purpose of this study was to identify, evaluate, compare, and synthesize the results published in the literature related to the clinical performance of removable dentures manufactured by CAD-CAM methods through two systematic reviews. The first review aimed to compare conventional and CAD-CAM complete dentures, and the second review aimed to analyze the performance of overdentures whose bars were fabricated with this technology. A systematic literature search of clinical studies comparing the conventional and CAD-CAM methods to manufactured dentures published until March 16, 2020, was conducted for the first review. Likewise, another comprehensive search of clinical articles evaluating the performance of bars used in overdentures, published until April 2021, was performed. Both studies used the following platforms: Pubmed/Medline, Web of Science, Cochrane Library, SciELO, and Embase databases following PRISMA criteria. In addition, both reviews were recorded in the International Prospective Registry of Systematic Reviews (PROSPERO) (1CDR: 42020202614/ 2ID 42021284190). Of the 1232 titles obtained by the first search, 6 articles were selected, and of the 64 titles obtained of the second search, 9 articles were selected. The outcomes demonstrated superior retention in dentures manufactured by the CAD-CAM system than dentures manufactured by conventional methods. Also, other studies reported that these dentures have a better adaptation to the mucosa, reduce clinical time, represent a lower cost, and offer a better experience and satisfaction to patients. The second review reported 100% of implant and prosthesis survival rates in titanium and zirconia bars manufactured by the CAD-CAM methods. Otherwise, the PEEK bars showed 80% of prosthesis survival rate. In addition, few biological complications were recorded in the CAD-CAM bars, however, between 5 to 19 years of use of prosthesis, were registered peri-implantitis in the CAD-CAM titanium bars (12.4%). Marginal bone loss and plaque and bleeding index were considered acceptable in the group which received overdentures with titanium CAD-CAM bars. The OHIP values of the CAD-CAM group significantly decreased after prosthesis installation, however, the group of implant-supported fixed prostheses showed better values (1.8 + 1.9). Furthermore, the patients and dentists demonstrated an important acceptance of overdentures with bars manufactured by the CAD-CAM system. This study concluded that, although the planning and the fabrication of CAD-CAM dentures are in progress, they presented a better performance and represent a lower cost when compared to conventional dentures. Similarly, the bars manufactured by the CAD-CAM methods demonstrated excellent performance in daily practice.